Membangun Semangat Belajar Kelompok Pada Anak -Anak Di Panti Asuhan Cermin Kasih Abadi - Agustia, Fitri; Aulina Lubis, Mia (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Group study is one of the group activities most often carried out by students, namely group study. This activity is considered very useful because it has many benefits, such as increasing intelligence, teaching how to lead effective discussions and teaching how to interact with fellow students. This research aims to identify and implement effective strategies to create enthusiasm for group learning in orphanage children. This research involves the active participation of children in group learning activities, taking into account their individual needs. The author sees that by building enthusiasm for group learning in children at the orphanage, the mirror of eternal love shows that the formation of a positive learning environment, the application of interesting learning methods, and strong emotional support can increase the enthusiasm for group learning. Apart from that, this research also emphasizes the importance of orphanage caregivers in creating an environment that is conducive to learning. There are many ways to increase the learning enthusiasm of a group of children. The method used in the application of this program activity uses a casework method through general intervention stages consisting of Engagement Intake Contract, Assessment, plan/Planning, intervention, evaluation, Termination. The results of this activity are children's participation in group learning activities, better academic achievement and social interactions